FAULT TOLERANT CONTROL FOR SENSOR FAULT OF A SINGLE-LINK FLEXIBLE MANIPULATOR SYSTEM (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper presents a new approach for sensor fault tolerant control (FTC) of a single-link flexible manipulator system (FMS) by using Finite Element Method (FEM). In this FTC scheme, a new control law is proposed where it is added to the nominal control. Â This research focuses on one element without any payload assumption in the modelling.Â  The FTC method is designed in such way that aims to reduce fault while maintaining nominal FMS controller without any changes in both faulty and fault free cases. This proposed FTC approach is achieved by augmenting Luenberger observer that is capable of estimating faults in fault detection and isolation (FDI) analysis. From the information provided by the FDI, fault magnitude is assessed by using Singular Value Decomposition (SVD) where this information is used in the fault compensation strategy. For the nominal FMS controller, Proportional- integral- derivative (PID) controller is used to control the FMS where it follows the desired hub angle. This work proved that the FTC approach is capable of reducing fault with both incipient and abrupt signals and in two types of faulty conditions where the sensor is having loss of effectiveness and totally malfunction. All the performances are compared with FTC with Unknown Input Observer (FTC-UIO) method via the integral of the absolute magnitude of error (IAE) method.